2010
DOI: 10.1063/1.3385278
|View full text |Cite
|
Sign up to set email alerts
|

Austenite–martensite interface in shape memory alloys

Abstract: A two-scale phase field simulation is developed for austenite–martensite interface to understand the effects of crystalline symmetry and geometric compatibilities on the reversibility of structural phase transformations in shape memory alloys. It is observed that when the middle eigenvalue of martensite transformation strain is equal to zero, an exact austenite–martensite interface is formed with negligible elastic energy. On the other hand, when the middle eigenvalue is different from 0, an inexact interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The realization of a large anhysteretic deformation of different (not only ferromagnetic) SMAs has a long-standing interest in both solid-state physics and materials science (see Refs. [24][25][26][27][28] and references therein). This interest is caused mainly by the commercial use of SMAs as the thermomechanical actuators whose actuation speed is limited by the width of thermal hysteresis of deformation whereby the SMA actuators exhibiting a low thermal hysteresis of deformation can be driven at a high actuation frequency.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The realization of a large anhysteretic deformation of different (not only ferromagnetic) SMAs has a long-standing interest in both solid-state physics and materials science (see Refs. [24][25][26][27][28] and references therein). This interest is caused mainly by the commercial use of SMAs as the thermomechanical actuators whose actuation speed is limited by the width of thermal hysteresis of deformation whereby the SMA actuators exhibiting a low thermal hysteresis of deformation can be driven at a high actuation frequency.…”
Section: Problem Statementmentioning
confidence: 99%
“…In particular, the possibility of anhysteretic MTs in the ternary and quaternary Ti-Ni-based alloys was searched intensively in view of their advanced engineering and biomedical applications. It has been shown that the thermal hysteresis characteristics obtained for these alloys crucially depend on the crystallographic features of MTs [24][25][26]28].…”
Section: Problem Statementmentioning
confidence: 99%
“…It has been applied successfully to study the twin structure of martensite Yang and Dayal, 2010) and austenitemartensite interface (Lei et al, 2010), domain structure of ferroelectrics Zhang et al, 2010), and coupled magnetoelastic domains in ferromagnetic shape memory alloys (Li et al, 2008a). One of the key advantages of this unconventional phase field method is that it makes the coupling among multiple order parameters much easier to implement, and thus is particularly suitable for studying multiferroics.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that when a thermomechanical load was applied in a martensitic NiAl system, the total recovery of deformation could be obtained by MD under the condition of periodic boundaries [11]. Considering the complexity of microstructure of martensite, the semiempirical potentialbased atomistic simulation approach is expected to play an important role in bridging a link between experiments and numerical models for understanding the transformation mechanism in SMAs [12][13][14].…”
Section: Introductionmentioning
confidence: 99%